THE CORRELATIONAL RELATIONSHIP BETWEEN PHYSICAL CHARACTERISTICS, ACTIVITIES, AND SENSE OF PLACE OF A PUBLIC SPACE - Rafidah Azzar Dea; Hanson Endra Kusuma (Journal of Architecture&ENVIRONMENT, 2021)
Public space is one of the important elements in a city to accommodate the citizen to do various things. However, it is not uncommon for public spaces to be ignored or unused by the community. Looking at this phenomenon, this study aims to look at the relationship between physical characteristics, activities, and sense of place of a public place. The research used qualitative methods in the first stage and quantitative methods in the second stage. The first stage explores the physical characteristics and activities in public spaces, as well as the user's perceived sense of place. The second stage reveals the correlational relationship between dimensions of physical characteristics, activities, and sense of place. From the results of the correlational analysis, it is revealed that the physical characteristics of the natural environment encourage a sense of meaningful place and encourage refreshing activities which also encourage a sense of meaningful place. In addition, productive activities are carried out by the physical character of the arts and kept away by the physical character of the social atmosphere and parking, as well as encouraging a sense of meaningful place. The physical character of the novelty encourages recreational activities and discourages socialization. In addition, the physical character of accessibility also encourages recreational and socialization activities. As for the physical character, many choices encourage socialization and consumptive activities which then create a sense of only knowing a space.